Differences between infants and adults in the social aetiology of wheeze. The ALSPAC Study Team. Avon Longitudinal Study of Pregnancy and Childhood. Issue 10 (1st October 1999) - Baker, D; Henderson, J
Abstract : OBJECTIVES: To compare the relation between relative deprivation, its associated social risk factors and the prevalence of wheeze in infancy and in adulthood. DESIGN: A cross sectional population study. SETTING: The three District Health Authorities of Bristol. SUBJECTS: A random sample of 1954 women stratified by age and housing tenure to be representative of women with children < 1 in Great Britain and selected from the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC). MAIN OUTCOME MEASURES: The prevalence of wheeze for infants at six months after birth and for their mothers and fathers at eight months postpartum. Potential mediators of the relation between relative deprivation and wheeze measured were overcrowded living conditions, number of other siblings in the household, damp or mouldy housing conditions, maternal and paternal smoking behaviour, and infant feeding practice. RESULTS: 63.4% (1239) of the sample lived in owner occupied/mortgaged accommodation (relatively affluent) and 36.6% (715) lived in council house/rented accommodation (relatively deprived). Wheeze was significantly more likely for infants living in council house/rented accommodation (chi 2 = 15.93, df = 1, p < 0.0001), their mothers (chi 2 = 9.28, df = 1, p < 0.001) and their fathers (chi 2 = 7.41, df = 1, p < 0.01). For those living in council house/rented accommodation backward stepwise logistic regression analyses showed that infants with other siblings in the household were significantly more likely to wheeze (OR = 1.83, 95% CI = 1.27, 2.65), as were infants whose mothers smoked (OR = 1.82, 95% CI = 1.30, 2.55) and those who were breast fed for less than three months (OR = 0.66, 95% CI = 0.44, 0.98). Mothers with a partner who smoked were significantly more likely to report wheeze (OR = 1.73, 95% CI = 1.05, 2.85). There was no independent association between the social factors included in the analysis and the likelihood of wheeze for fathers. CONCLUSIONS: This study identified differences in the social factors associated with a higher prevalence of wheeze in infancy and in adulthood; results suggested that this symptom was commonly linked to infection in infancy, but not in adulthood. While environmental tobacco smoke was associated with a higher prevalence of wheeze in infancy and in adulthood, this does not necessarily indicate a common underlying mechanism; possible explanations are discussed.